Psychometric Properties of the Spanish Version of Psychosocial Impact of Assistive Devices Scale in a Large Sample of People With Neuromuscular, Neurological, or Hearing Disabilities - Díez, Emiliano; Jiménez-Arberas, Estíbaliz; Pousada, Thais (Frontiers in Psychology, 2021)
Assistive technology (AT) is any device, software, or equipment designed for and used by individuals with disabilities to engage in everyday activities and achieve independence. However, the usefulness of those technology-based or supported treatments is a complex issue that has led to the development of various conceptual models for assistive technology outcomes research and practice as well as different assessment tools that help to explore the effect of technology on people's lives. One of those instruments is the Psychosocial Impact of Assistive Device Scale (PIADS), a 26-item questionnaire that measures the psychosocial impact of interventions, using assistive devices in three quality-of-life domains: competence, adaptability, and self-esteem. PIADS scale has been translated and adapted to several languages, and it has been successfully used to measure AT outcomes in different disability profiles to predict abandonment or even as a relevant determinant of future adoption of eHealth. Quinteiro (2010) adapted PIADS to Spanish for the first time, although no studies have yet been published to systematically study its psychometric properties. Therefore, the purpose of this study was to evaluate measurement properties of the Spanish version of PIADS scale by means of a dataset obtained from its application to a large sample (n = 417) of people with neuromuscular, neurological, or hearing disabilities that used different assistive devices. The results will provide valuable indicators about the measurement quality of the Spanish PIADS scale and will help to promote the use of reliable and valid AT outcome assessment tools for research and clinical purposes.